Fa'iliyat al-khidmat al-ijtima'iyah fi mu'assasat al-tarbiyah wa-tawjih al-ahdath al-manharifin bi-Libya wa-qudratuha 'ala 'ilajihim : dirasah maydaniyah bi-madinah Tarabulus = The effectiveness of social services in Libyan delinquents educational and guidance institutions : a case study in Tripoli/ Amal Emhamad Ab. Hammyd - Hammyd, Amal Emhamad Ab. (2011)
Nation’s progress in all life aspects depends on the performance of its young people. Thus, juvenile delinquency is one of the serious problems that lead to decline the level of such progress. The current study seeks to examine the effectiveness of services offered in the institutions for juvenile education and guidance in Libya? More specifically, it attempts to answer the following questions: What are the services provided at the institutions for education and guidance of juvenile delinquents? To what extent the social services provided to juvenile delinquents at the institutions for education and guidance of juvenile delinquents are effective? What are the difficulties facing those who provide services at the institutions for education and guidance of juvenile delinquents? Are there significant differences in the level of effectiveness in the institutions of education and guidance of juvenile delinquents due to gender and institution? To what extent the regulations within the institutions for education and guidance of juvenile delinquents are applied? This study is descriptive in nature. A sample of 201 respondents was selected using the social survey method. It was divided into three categories: 116 juvenile delinquents, 60 specialists (social specialists and psychologists, social supervisors, teachers, activity supervisors, preachers, doctors, pharmacists, nurses, and skilled workers), and 25 administration staff. An interview and three questionnaires were used for data collection. To answer the research questions, descriptive analyses, factor analyses, regression, T-test, and Pearson correlation were used. The results showed that the highest mean of services was that of educational services, followed by religious, medical, cultural, sport, and general services respectively. A good value (77.5 %) was given to the effectiveness of the services offered at the institutions for education and guidance of juvenile delinquents. With regard to the difficulties facing the specialists were as follows: insufficient training workshops for staff, lack of incentives for staff, and insufficient technical and administrative supervision. The results also indicated that there was no significant difference in the effectiveness level due to gender. However, there were significant differences between the institutions in some variables in favor of males, as they scored higher means. Finally, the results revealed that the institutions were partially applying the internal list of regulations.